Validity and Reliability of 10-Hz Global Positioning System to Assess In-line Movement and Change of Direction - Nikolaidis, Pantelis T.; Clemente, Filipe M.; van der Linden, Cornelis M. I.; Rosemann, Thomas; Knechtle, Beat (Frontiers in Physiology, 2018)
The objectives of the present study were to examine the validity and reliability of the 10Hz Johan GPS unit in assessing in-line movement and change of direction. The validity was tested against the criterion measure of 200m track-and-field (track-and-field athletes, n=8) and 20m shuttle run endurance test (female soccer players, n=20). Intra-unit and inter-unit reliability was tested by intra-class correlation coefficient (ICC) and coefficient of variation (CV), respectively. An analysis of variance examined differences between the GPS measurement and five laps of 200m at 15km/h, and t-test examined differences between the GPS measurement and 20m shuttle run endurance test. The difference between the GPS measurement and 200m distance ranged from -0.13±3.94m (95% CI -3.42; 3.17) in the first lap to 2.13±2.64m (95% CI -0.08; 4.33) in the fifth lap. A good intra-unit reliability was observed in 200m (ICC=0.833, 95% CI 0.535; 0.962). Inter-unit CV ranged from 1.31% (fifth lap) to 2.20% (third lap). The difference between the GPS measurement and 20m shuttle run endurance test ranged from 0.33±4.16m (95% CI -10.01; 10.68) in 11.5km/h to 9.00±5.30m (95% CI 6.44; 11.56) in 8.0km/h. A moderate intra-unit reliability was shown in the second and third stage of the 20m shuttle run endurance test (ICC=0.718, 95% CI 0.222;0.898) and good reliability in the fifth, sixth, seventh and eighth (ICC=0.831, 95% CI -0.229;0.996). Inter-unit CV ranged from 2.08% (11.5km/h) to 3.92% (8.5km/h). Based on these findings, it was concluded that the 10Hz Johan system offers an affordable valid and reliable tool for coaches and fitness trainers to monitor training and performance.